MATHEMATICAL MODELS AND METHODS OF OFFICE PROJECT MANAGEMENT - and (Municipal economy of cities. Series: «Economy science», 2013)
We analyze the complex tasks of office management of construction projects in the context of current requirements for the control system as an integrated structured and functionally complete. Defined logical sequence solving , their characteristics , principles and evaluation. Because the problem with the character bahatokryterialnosti and uncertainties solutions to their proposed method of analysis of hierarchies and methods of evaluation and optimization in terms of varying degrees of certainty input data .